Risk of Severe Acute Localized Reactions for Different Intraarticular Hyaluronic Acid Knee Injections in a Real-World Setting. (December 2021) - Ong, Kevin L.; Farr, Jack; Gudeman, Andrew S.; Murray, Iain R.; McIntyre, Louis F.; Hummer, Charles D.; Ngai, Wilson; Lau, Edmund; Altman, Roy D.; Sherman, Seth L.
Objective: Case reports of severe acute localized reactions (SALR) following intraarticular (IA) hyaluronic acid (HA) injections for knee osteoarthritis (OA) have been described. We compared surrogate SALR measures between patients using hylan G-F 20 and specific non-hylan G-F 20 HA products. Design: Knee OA patients were identified from the Optum Clinformatics dataset (January 2006 to June 2016), stratified into hylan G-F 20 and non-hylan G-F 20 HA users, matched by single or multiple injection products. Occurrences of surrogate SALR measures including inflammation/infection, intraarticular corticosteroid (CS) injections, arthrocentesis/aspiration, arthrotomy/incision and drainage, and arthroscopy were evaluated within 3 days post-HA. Results: Based on 694, 404 HA injections, inflammation/infection rate was rare within 3 days of HA (up to 0.03%), with no statistical differences between hylan G-F 20 and non-hylan G-F 20 groups (matched by single or multiple injection products). The risk of knee arthrotomy/incision and drainage, arthroscopy, or arthrocentesis for hylan G-F 20 (2 mL) 3 weekly injection patients was lower than Hyalgan/Supartz and Orthovisc patients, but greater than Euflexxa patients. Overall, we found that Hylan G-F 20 (2 mL) 3 weekly injection had lower SALR rates compared to Hyalgan/Supartz and Orthovisc. However, Hylan G-F 20 (2 mL) 3 weekly injection had slightly higher rates of SALR when compared to Euflexxa. Among the single injection products, Hylan G-F 20 (6 mL) single injection had lower rates of SALR than Monovisc and Gel-One. Conclusions: This study shows no clear correlation between avian-derived or cross-linked products and SALR and provides evidence against avian-derived products or crosslinking as a source for these reactions.